BUREAUCRATIC REFORM: ANALYSIS OF WORK FROM ANYWHERE POLICY PLANS FOR ASN - Mahir Pratama; Lisman Manurung (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2022)
The government plans a WFA policy for ASN in 2023. This is based on a good assessment of WFH and WFO during the COVID-19 pandemic. This plan is also in line with the agenda of Bureaucratic Reform and e-government. The purpose of this paper is to find out the policy narrative developed by the government for WFA and the potential challenges that will be faced by the government as well as to what extent the government is ready to implement WFA policies for ASN. The method used is a postpositivist approach with Narrative Policy Analysis (NPA) analytical instruments with secondary data obtained from scientific journals, mass media and relevant public data. As a result, the government must make a comprehensive study related to WFA and issue special rules for WFA that regulate the system of performance, assessment, monitoring, and evaluation. It also requires job criteria and ASN who can perform WFA. Improving the quality of human resources and digital infrastructure is also a requirement for conducting WFA.